2014
DOI: 10.1371/journal.pone.0116284
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Extent of Carotid Atherosclerosis in Patients Treated with Radiotherapy for Nasopharyngeal Carcinoma

Abstract: ObjectiveTo determine the predictors of the extent of carotid atherosclerosis in patients treated with radiotherapy (RT) for nasopharyngeal carcinoma (NPC).MethodsThe present study investigated 129 post-RT NPC patients. Carotid atherosclerotic parameters, such as carotid intima-media thickness, carotid arterial stiffness and carotid plaque burden (plaque score, the presence of plaque and ≥50% stenosis) were assessed using ultrasonography. The association between carotid atherosclerotic parameters and nine pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…The difference may be attributed to different measurement methods as was discussed by the authors. Another study identified carotid stenosis (≥50%) in 20.9% of 129 NPC patients who underwent 2D-RT, similar with our result for all patients 20 . However, their published incidence rate was lower than ours for the 2D-RT group and higher for the IMRT group.…”
Section: Discussionsupporting
confidence: 91%
“…The difference may be attributed to different measurement methods as was discussed by the authors. Another study identified carotid stenosis (≥50%) in 20.9% of 129 NPC patients who underwent 2D-RT, similar with our result for all patients 20 . However, their published incidence rate was lower than ours for the 2D-RT group and higher for the IMRT group.…”
Section: Discussionsupporting
confidence: 91%
“…Progressive carotid stenosis was observed over several years after radiotherapy [5,10,17], with the same observation being made for the general plaque burden [18,19]. With regards to IMT, long-term progression was seen in some but not all studies [19][20][21][22]. Most of these results, however, are based on cross-sectional studies.…”
Section: Discussionmentioning
confidence: 63%
“…The deleterious effect of radio(chemo)therapy on the carotid arteries is well known [11,[14][15][16]. Progressive carotid stenosis was observed over several years after radiotherapy [5,10,17], with the same observation being made for the general plaque burden [18,19]. With regards to IMT, long-term progression was seen in some but not all studies [19][20][21][22].…”
Section: Discussionmentioning
confidence: 91%
“…[ 17 ] Intima-media thickness of the common carotid artery is a marker of early changes in atherosclerosis, which could be measured by modern high-resolution ultrasound machines and has proved to be a powerful predictor of future cerebrovascular disease. [ 5 ] Early changes in postradiation carotid injury are asymptomatic; hence, it is recommended to regularly monitor the intima-media thickness of the common carotid artery after irradiation and perform timely interventions to avoid the occurrence of radiogenic vascular events.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 , 4 ] Exposure to radiation can result in accelerated atherosclerosis; both large extracranial arteries and intracranial arteries are reportedly damaged after radiotherapy, which may further lead to stenosis of the cranial arteries and increased risk of cerebral infarction or transient ischemic attack. [ 5 ] Therefore, radiation-induced cerebral infarction often develops after radiation treatment. [ 6 ] On the contrary, the hypothalamic-pituitary axis is an extraordinarily radiosensitive range of the central nervous system, and hypopituitarism is usually induced by radiotherapy.…”
Section: Introductionmentioning
confidence: 99%